Evidence and control of bifurcations in a respiratory system - Goldin, Matías Alejandro (2014)
The comprehension of motor activities that give rise to complex behavior are of great interest. A widely used animal model to study them is the one of singing birds, where respiration plays a fundamental role. Different mechanisms have been proposed to account for the dynamical origin of these motor gestures. In this work, we study the temporal signals of the pressure gestures used by domestic canaries (Serinus canaria) to perform their songs. Their analysis revealed that ubiquitous occurring transitions between syllables can be interpreted as the bifurcations of a low dimensional dynamical system. This provides evidence supporting a model where different nonlinearly interacting timescales participate.